Hubungan Antara Regulasi Diri Dengan Penyesuaian Diri Santri Pondok Pesantren Di Surakarta - Isnaini, Farikah, Dra. Partini, M.Si (2017)
Islamic Boarding School is an Institution of Islamic Education which there is a Kyai, he's teaching and educating the student or santri with all of religion science and another science. Santri who has been living in the Islamic Boarding School demanded by it self to adaptation with new environment, we call it with Islamic Boarding School. But in the reality, the new student or new santri has obstacle in the adaptation on it. One else factor that can be influence the adjustment is personality. In the personality, self regulated is a factor that can be influence the adjustment. The aim of this study is (1) Find the relation toward level of adjustment and level of self regulated in Islamic Boarding School, (2) Find the student's level of adjustment in Islamic Boarding School, (3) Find the student's level of self regulated in Islamic Boarding School, (4) Find the effectively impact of the both in Islamic Boarding School. Subject of this study has using Cluster random sampling, 7 Islamic Boarding School that selected, 2 Islamic Boarding School that consist of 8 classes and each of 4 classes. Subjects in this study was 141 that divided of 77 subjects on Al-muayyad islamic boarding school and 64 subjects Ta'mirul islamic boarding school. Scale that i used in thi study is self adjustment and scale self regulation. Hypothesis in this study is there was positively relation toward adjustment and self regulated of student or santri in Islamic Boarding School. The technique of taking sample was using product momet. The result of this study has coefficient score 0.546 with probability = 0,000 (p<0,01) it means Adjustment has relation toward self regulated positively and significant. The results in this study was variable self adjustment classified in high categories and variable self regulation in moderate categories. It based on 29,81% effectively influenfed by self regulated and the adjustment. Then another variables except self regulated that gives impact to adjustment showed on 70.19%